Effect of inhomogeneities on backward and forward Brillouin scattering in Photonic Crystal Fibers - Stiller, Birgit; Delque, Michael; Lee, Minw.; Mafang, Stella Foaleng; Beugnot, Jean-Charles; Kudlinski, Alexandre; Thevenaz, Luc; Maillotte, Herve; Sylvestre, Thibaut (Proceedings of SPIE - The International Society for Optical Engineering, 2010)
Photonic Crystal Fibers (PCF) play a crucial role for fundamental investigations such as acousto-optical interactions as well as for applications, such as distributed sensors. One limiting factor for these experiments is the fiber inhomogeneity owing to the drawing process. In this paper we study the effect of structural irregularities on both the backward and forward Brillouin scattering by comparing two PCFs drawn with different parameters, in order to minimize diameter fluctuations. We fully characterize their Brillouin properties including the backward Brillouin spectrum, the Brillouin threshold, a distributed measurement along the fibers and polarized Guided Acoustic Wave Brillouin Scattering (GAWBS). In the Brillouin spectrum we observe a single peak as in a single-mode fiber whereas former investigations have often shown a multiple peak spectrum in PCFs with small core. The theoretical and experimental values for the Brillouin threshold are in good agreement, which results from the single peak spectrum. By using a Brillouin echoes distributed sensing system (BEDS), we also investigate the Brillouin spectrum along the fiber with a high spatial resolution of 30 cm. Our results reveal a clear-cut difference between the distributed measurements in the two fibers and confirm the previous experiments. In the same way the GAWBS allows us to estimate the uniformity of the fibers. The spectra show a main peak at about 750 MHz, in accordance with theoretical simulations of the acoustic mode and of the elasto-optical coefficient. The fiber inhomogeneity impacts on the stability and the quality factor of the measured GAWBS spectra. We finally show that the peak frequency of the trapped acoustic mode is more related to the optical effective area rather than the core diameter of the PCF. Thus measuring the main GAWBS peak can be applied for the precise measurement of the effective area of PCFs. © 2010 SPIE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin scattering; Distributed sensing; Photonic Crystal Fibers